(untitled) (Journal of Atomic and Molecular Sciences, 2015)
The femtosecond laser ablation process and induced breakdown spectroscopy of transition metal Ti in air background has been investigated systematically. The ablation process is simulated by means of a three-dimensional two temperature model (3D-TTM). The time-resolved spectroscopy is employed to determine the characteristics of plasma during its evolution. The time-of-flight spectroscopy (TOFS) is also used to characterize the plasma expansion. The evolution behaviors of the plasma and its spectral characteristics have been analyzed as a function of pressure. It is shown that the component, expansion behavior and characteristics of the plasma have strong pressure dependences. The results are discussed in terms of the interaction mechanisms between ambient air and plasma species.